Livestock policies for the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The seven-year Uruguay Round of negotiations on the General Agreement on Tariffs and Trade (GATT) was concluded in April 1994 and for the first time the agreement included agricultural commodities. The aims of the agreement concerning agriculture...